Pendampingan dan Penguatan Usaha Mikro Kecil dan Menengah (UMKM) Asosiasi Pangan Riau (ASPARI) Terdampak Pandemi Covid-19 di Kota Pekanbaru - Kornita, Sri Endang; Pratiwi, Yulia; Livi, Aldisa Sipti; Fahrizal, Syalsa Dwita; Asrin, Wirdhatul Jannah; Asrianda, Muhammad Akbar; Biila, Umaima Salsa; Pratama, Yudha; Suryani, Diannisa Mahiru; Bahagiana, Berkah; Lazuardi, Muhammad Turangga (Wahana Jurnal Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic has greatly affected the MSME economy, such as the decline in market demand due to policies related to activities outside the home. The choice of the main content raised in the research requires external parties as partners to support the realization of the solution, so ASPARI was chosen. The Riau Food Industry Association or better known as ASPARI is a gathering of actors in the local sector which was founded in 1996. It was initiated by actors in the food sector in Riau Province. The research method used is descriptive with a descriptive approach to sustainability. The data collection method used is in the form of reports and documentation. The object used in this study is an association which is a forum for food MSMEs in Riau Province, namely as ASPARI. The research subjects are several MSMEs in Pekanbaru City which are members of ASPARI. Researchers took data sources using purposive sampling technique. Various assistance efforts to MSMEs that have an impact on Covid-19 as well as collaborating with the ASPARI (Riau Food Association) by implementing various strategies, including the following: Digital Product Marketing, Create Attractive Packaging and Logo Designs, Business Financial Management.